Komunikasi pemasaran di pemerintahan dan pengaruhnya terhadap keputusan wisatawan domestik - Rafa'al, Mubaddilah; Simabur, Lisda Ariani; Sangadji, Suwandi S (Jurnal Komunikasi Profesional, 2021)
This study aims to determine the effect of marketing communications at the Tourism Office of West Halmahera (Halbar) on the decision of domestic tourists to choose a tourist destination for Halbar. In this study apply the theory of Integrated Marketing Communication. The subjects of this study were domestic tourists who were exposed to marketing communications carried out by the Halbar Regency Tourism Office with the age provisions of 20 -5i years. The research sample amounted to 100 respondents. Survey is the method used in this study with a questionnaire as an instrument to collect data. Where variable X is Marketing Communication and variable X is the decision of domestic tourists. The analysis technique uses a distribution table, while to test the hypothesis using Correlation-Rank-Order, significant test uses t-test, and calculates the Strength of Influence (KP). The results of the study indicate that the hypothesis proposed by the researcher is that there is an influence of marketing communications from the Halbar Tourism Office on the decision of domestic tourists to choose an accepted tourist destination (0.396), with the results of the calculation of rho (rs) = 0.396, it can be stated that there is a significant relationship between the two variables. the. Based on the results of the t-test, the correlation obtained is significant, meaning that the marketing communication of the Halbar Regency Office affects the decisions of domestic tourists. Furthermore, to calculate the power of influence (KP), namely the influence of the relationship between the marketing communications of the Halbar Regency Tourism Office on the decisions of domestic tourists, it is 15.68%.